Separate phase-locking and coherent combining of two laser diodes in a Michelson cavity - Schimmel, G.; Doyen, I.; Janicot, S.; Ramirez, L.P.; Hanna, M.; Georges, P.; Lucas-Leclin, G.; Vilokkinen, V.; Melanen, P.; Uusimaa, P.; Decker, J.; Crump, P.; et al. (2015)
We describe a new coherent beam combining architecture based on passive phase-locking of two laser diodes in a Michelson external cavity on their rear facet, and their coherent combination on the front facet. As a proof-of-principle, two ridge lasers have been coherently combined with >90 % efficiency. The phase-locking range, and the resistance of the external cavity to perturbations have been thoroughly investigated. The combined power has been stabilized over more than 15 min with an optical feedback as well as with an automatic adjustment of the driving currents. Furthermore, two high-brightness high-power tapered laser diodes have been coherently combined in a similar arrangement; the combining efficiency is 70% and results in an output power of 4 W. We believe that this new configuration combines the simplicity of passive self-organizing architectures with the optical efficiency of master-oscillator power-amplifier ones.